The Effect of Self-Efficacy, Creativity, and Learning Motivation on The Religiosity of State High School Students - Helfinasyam Batubara; Rusydi Ananda; Retno Sayekti (Pascasarjana Universitas KH. Abdul Chalim, 2026)
Religiosity plays a crucial role in shaping students’ moral character; however, in the contemporary educational context, it is increasingly influenced by internal psychological and academic factors rather than solely by formal religious instruction. This study aims to examine the influence of self-efficacy, creativity, and learning motivation on the religiosity of public senior high school students in Central Tapanuli Regency. The research employed a quantitative approach with a positivist paradigm and a correlational design. A total of 313 students were selected from a population of 1,424 using proportional random sampling. Data were collected through a validated and reliable Likert-scale questionnaire and analyzed using descriptive statistics and multiple linear regression. The findings reveal that self-efficacy, creativity, and learning motivation simultaneously have a significant effect on students’ religiosity, accounting for 51.1% of the variance. Partially, all variables show positive and significant effects, with creativity emerging as the strongest predictor, followed by learning motivation and self-efficacy. These results indicate that students’ religiosity is shaped through the interaction of psychological beliefs, creative thinking, and motivational engagement. The study implies that enhancing students’ religiosity requires a holistic educational approach that integrates psychological development with religious education. Schools are therefore encouraged to design learning environments that foster self-efficacy, support creative expression, and strengthen intrinsic motivation to promote sustainable religious character development.